Physical and thermomechanical properties of oil palm ash-filled unsaturated polyester composites - Ibrahim, Mohd Shukri (2012)
The main advantages of the oil palm ash are its availability at abundance, no cost material, high aspect ratio and good performance in high thermal condition. This research investigates the physical characteristics of oil palm ash filler and the effects of filler contents on mechanical and thermal properties of oil palm ash filled unsaturated polyester composite (UP/OPA). The composite specimens made of different filler contents of 0, 10, 20 and 30% of oil palm ash were prepared. All of these composites were fabricated using a conventional hand lay up technique. The mechanical tests such as tensile and flexural were carried out in according with American Society of Testing Material D 5083 and American Society of Testing Material D 790 standards respectively. Scanning electron microscope was used to study the surface morphology of UP/OPA composites of the fractured surface for tensile and flexural tests. The results of the experiments showed that the increasing of filler contents i.e. 0, 10, 20 and 30% of oil palm ash had significant effects on reduction of tensile strength (26.8MPa, 21MPa, 17MPa and 13MPa); flexural strength (88.48MPa, 78.17MPa, 71.70MPa and 62.5MPa) and elongation at break (5.55%, 3.11%, 2.52% and 2.36%); and increase of tensile modulus (3.75MPa, 3.9MPa, 4.35MPa and 4.99MPa) and flexural modulus (200MPa,214MPa, 222MPa and 233MPa) of the UP/OPA composites respectively. Investigation on thermal properties of UP/OPA composite involved thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC) in order to investigate temperatures at maximum mass loss and to determine glass transition temperature (Tg) of the UP/OPA composites. The results have shown that increasing of filler contents i.e. 0, 10, 20 and 30% of oil palm ash for UP/OPA composites had improved their thermal stability because their initial decomposition of temperatures at 5% mass loss were increased 293.55, 356.64, 375.59 and 401.72°C respectively, temperatures at maximum mass loss were also increased 436.64, 460.90, 468.01 and 476.23°C respectively and glass transition temperatures slightly increased from 185.4 to 191°C with the additions of fillers for up to 30%.